2010
DOI: 10.1073/pnas.1016814108
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced tumorigenesis in the colon is regulated by caspase-1 and NLRC4

Abstract: Chronic inflammation is a known risk factor for tumorigenesis, yet the precise mechanism of this association is currently unknown. The inflammasome, a multiprotein complex formed by NOD-like receptor (NLR) family members, has recently been shown to orchestrate multiple innate and adaptive immune responses, yet its potential role in inflammation-induced cancer has been little studied. Using the azoxymethane and dextran sodium sulfate colitis-associated colorectal cancer model, we show that caspase-1-deficient (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
372
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(385 citation statements)
references
References 39 publications
10
372
1
2
Order By: Relevance
“…Further evidence for its role as a tumor suppressor comes from a mouse model of colitis-associated colorectal cancer. 135 Caspase-1-deficient mice showed enhanced tumor formation, characterized by early stage increase in epithelial cell proliferation in the colon and reduced apoptosis during advanced disease stage. 135 Recent studies have shown that originally generated caspase-1-deficient mice also harbor a mutation in the caspase-11 locus, which mediates LPS-induced lethality in these mice.…”
Section: Caspases In Tumorigenesismentioning
confidence: 99%
“…Further evidence for its role as a tumor suppressor comes from a mouse model of colitis-associated colorectal cancer. 135 Caspase-1-deficient mice showed enhanced tumor formation, characterized by early stage increase in epithelial cell proliferation in the colon and reduced apoptosis during advanced disease stage. 135 Recent studies have shown that originally generated caspase-1-deficient mice also harbor a mutation in the caspase-11 locus, which mediates LPS-induced lethality in these mice.…”
Section: Caspases In Tumorigenesismentioning
confidence: 99%
“…In one study, this was dependent on NLRC4 and was epithelial intrinsic rather than inflammation mediated (Hu et al, 2010), whereas, in another study, increased tumorigenesis involved NLRP3 and was inflammation and hematopoietic cell-dependent (Allen et al, 2010). Such discrepancies are suggested to arise from differences in microbiota between facilities or use of WT mice from external sources (Ubeda et al, 2012), but could also arise from opposing functions of inflammasome components in different tissues, which has been demonstrated in a skin tumorigenesis model (Drexler et al, 2012).…”
mentioning
confidence: 99%
“…Several Nod-like receptors (NLRs) have previously been implicated in colon inflammation and tumorigenesis, mostly in protective roles (Allen et al, 2010;Hu et al, 2010;Chen et al, 2011;Elinav et al, 2011;Zaki et al, 2011;Carvalho et al, 2012). In some cases, this has been attributed to reduced inflammasomemediated release of IL-18, which is protective for the colonic epithelium (Allen et al, 2010;Dupaul-Chicoine et al, 2010).…”
mentioning
confidence: 99%
“…Hu et al demonstrated [82] the protective effect of NLRC4 in azoxymethane-dextran sodium sulfate -induced colitis-associated colorectal cancer. This effect was independent of inflammation, which was the same in NLRC4-deficient and wild-type mice.…”
Section: Resultsmentioning
confidence: 99%
“…This effect was independent of inflammation, which was the same in NLRC4-deficient and wild-type mice. The protective role came from NLRC4 originating from non-hematopoietic cell compartment [82]. They proposed that epithelial NLRC4 signaling regulates apoptosis thorough p53 activation [83].…”
Section: Resultsmentioning
confidence: 99%